1998
DOI: 10.1007/s10787-998-0012-6
|View full text |Cite
|
Sign up to set email alerts
|

Sjögren’s syndrome: History, clinical and pathological features

Abstract: The history, ocular and oral clinical features, and histopathology of Sjögren's syndrome are described. Primary Sjögren's syndrome is defined when only the ocular and oral components are present, while the secondary form refers to the association with a connective tissue disorder, especially rheumatoid arthritis, or other illness such as AIDS, hepatitis C infection, or biliary cirrhosis. Sjögren's syndrome is a common, but often overlooked disorder. Patients with severe disease run a forty-times risk of develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Although the primary clinical features of this disease were described by W.B. Hadden in 1888, the sicca syndrome as a systemic disease was first appreciated in 1933 by a Swedish ophthalmologist Henrik Samuel Conrad Sjögren [7]. In his thesis, Dr. Sjögren clarified that keratoconjunctivitis sicca, coined by himself, had no relation to xerophthalmia resulting from vitamin A deficiency.…”
Section: Sjogren’s Syndromementioning
confidence: 99%
“…Although the primary clinical features of this disease were described by W.B. Hadden in 1888, the sicca syndrome as a systemic disease was first appreciated in 1933 by a Swedish ophthalmologist Henrik Samuel Conrad Sjögren [7]. In his thesis, Dr. Sjögren clarified that keratoconjunctivitis sicca, coined by himself, had no relation to xerophthalmia resulting from vitamin A deficiency.…”
Section: Sjogren’s Syndromementioning
confidence: 99%
“… 33 , 34 As expected, the most common diagnosis was KCS, as it has been reported. 32 , 35–37 Similarly, other ophthalmologic diagnoses had been described. Akpek et al reported the following ocular involvement in a group of SS patients: corneal perforation (3.1%), corneal ulcer (0.6%), corneal scarring (4.3%), papillary conjunctivitis (7.4%), follicular conjunctivitis (2.5%), uveitis (1.2%), scleritis/episcleritis (0.6%), optic neuropathy (1.8%), and orbital inflammation (1.8%).…”
Section: Discussionmentioning
confidence: 91%
“…Sjogren's syndrome (SS) is a chronic, progressive, and systemic autoinflammatory disease, with exocrine (mainly salivary and lacrimal) glands as the main target organs, leading to the development of sicca symptoms [1,2]. They are the main clinical feature of the disease.…”
Section: Introductionmentioning
confidence: 99%